Xmas-2 Protein, the Core Protein of the TREX-2 mRNA Export Complex, Does not Determine the Specificity of ras2 mRNA Binding by the Complex. - Kurshakova, M.M.; Vdovina, Y.A.; Georgieva, S.G.; Kopytova, D.V. (Doklady. Biochemistry and Biophysics, 2024)
The TREX-2 complex of eukaryotes is responsible for the export of a wide range of mRNAs from the nucleus to the cytoplasm. Previously, we showed that a subunit of the D. melanogaster TREX-2 complex, the PCID2 protein, has a domain that specifically interacts with RNA. However, it remains unknown whether other components of the complex are involved in interaction with and recognition of the target mRNA. In the present study, we determined the role of Xmas-2, the core structural subunit of the complex, in the specific recognition of ras2 mRNA fragments. In this work, we showed that Xmas-2 interacts with ras2 mRNA independently of other subunits of the complex. We showed that RNA-binding domains are located in both the N-terminal domain and the C-terminal domain of Xmas-2. However, the interaction of the protein with ras2 mRNA fragments is independent of RNA sequence and structure and is nonspecific. Thus, the Xmas-2 subunit is not involved in the recognition of specific RNA sequences by the complex.